Digital Storytelling Methods to Increase Student Interest in Learning Islamic Religious Education - Sukiani; Irwan; Syafruddin (Yayasan Letiges Konsultan Sosial, 2026)
This study aims to describe and analyze the application of the digital storytelling method in Islamic Religious Education learning and identify its influence on students' learning interest. This study uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Observations were conducted on eighth-grade students, while interviews were conducted with six teachers and three students. The research data consists of primary and secondary data analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that applying the digital storytelling method can increase students' learning interest, especially among those who previously had low learning interest. This increase is evident in students' enthusiasm for learning, their active participation in discussions, and their increased interest in Islamic Religious Education materials. This study provides a theoretical contribution by strengthening the use of the digital storytelling method to increase students' interest in learning Islamic Religious Education subjects. The study's findings indicate that applying the digital storytelling method can be an effective alternative for creating more interactive and engaging learning experiences. Supporting factors for the application of this method include the availability of learning facilities and student readiness, while inhibiting factors are limited time and teachers' ability to apply the digital storytelling method.